2021
DOI: 10.3390/diagnostics11111962
|View full text |Cite
|
Sign up to set email alerts
|

Automated COVID-19 and Heart Failure Detection Using DNA Pattern Technique with Cough Sounds

Abstract: COVID-19 and heart failure (HF) are common disorders and although they share some similar symptoms, they require different treatments. Accurate diagnosis of these disorders is crucial for disease management, including patient isolation to curb infection spread of COVID-19. In this work, we aim to develop a computer-aided diagnostic system that can accurately differentiate these three classes (normal, COVID-19 and HF) using cough sounds. A novel handcrafted model was used to classify COVID-19 vs. healthy (Case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Nonetheless, this modality is not useful when the pleura is spared from the pneumonic pathology during the early course of the disease [ 297 ]. Recent developments in the diagnosis of COVID-19 using signals such as respiratory sounds, speech signals, and coughing sounds, have also attracted many researchers [ 298 , 299 ]. Furthermore, in the future, this can be combined with other imaging modalities and signals to enhance the performance of the system using various deep learning approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this modality is not useful when the pleura is spared from the pneumonic pathology during the early course of the disease [ 297 ]. Recent developments in the diagnosis of COVID-19 using signals such as respiratory sounds, speech signals, and coughing sounds, have also attracted many researchers [ 298 , 299 ]. Furthermore, in the future, this can be combined with other imaging modalities and signals to enhance the performance of the system using various deep learning approaches.…”
Section: Discussionmentioning
confidence: 99%
“… [9] initiated an automated diagnosis system to differentiate between COVID-19 and heart failure depending on the pattern of cough sounds. They proposed a model to generate features deploying DNA pattern.…”
Section: Related Workmentioning
confidence: 99%
“…The authors employed a random forest classifier with nearly 90% accuracy. Kobat et al [13] used a graph-based local feature generator, an iterative maximum relevance minimal redundancy iterative feature selector, and the k-nearest neighbor classifier for cough sound-based COVID-19, heart failure, and healthy subject discrimination. For the COVID-19 vs. healthy, heart failure vs. healthy, and COVID-19 vs. heart failure vs. healthy classes, the authors reported accuracies of 100.0 %, 99.38 %, and 99.49 %, respectively.…”
Section: Introductionmentioning
confidence: 99%